2021
DOI: 10.1158/2159-8290.cd-20-1690
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Screens for Suppressors of Anoikis Identify IL1RAP as a Promising Surface Target in Ewing Sarcoma

Abstract: Cancer cells must overcome anoikis (detachment-induced death) to successfully metastasize. Using proteomic screens, we found that distinct oncoproteins upregulate IL-1 receptor accessory protein (IL1RAP) to suppress anoikis. IL1RAP is directly induced by oncogenic fusions of Ewing sarcoma (EwS), a highly metastatic childhood sarcoma. IL1RAP inactivation triggers anoikis and impedes metastatic dissemination of EwS cells. Mechanistically, IL1RAP binds the cell surface system X c transporter to enhance exogenous … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
85
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(87 citation statements)
references
References 64 publications
1
85
1
Order By: Relevance
“…In addition, several lines of recently emerging data underline the importance of CSE in various aspects of breast cancer biology including growth, metastasis and the development of multidrug resistance [ [220] , [221] , [222] , [223] , [224] , [225] ]. Finally, recent studies demonstrate the inhibitory effect of CSE inhibition and/or silencing in models of Ewing sarcoma [ 226 ] and glioma [ 227 ].…”
Section: Roles Of Cse and 3-mst In Cancer; Interactions With Cbsmentioning
confidence: 99%
“…In addition, several lines of recently emerging data underline the importance of CSE in various aspects of breast cancer biology including growth, metastasis and the development of multidrug resistance [ [220] , [221] , [222] , [223] , [224] , [225] ]. Finally, recent studies demonstrate the inhibitory effect of CSE inhibition and/or silencing in models of Ewing sarcoma [ 226 ] and glioma [ 227 ].…”
Section: Roles Of Cse and 3-mst In Cancer; Interactions With Cbsmentioning
confidence: 99%
“…In this work, we investigated IL-1RAP, a novel and unexplored AML cell surface marker expressed by leukemia cells but not by the healthy HSCs or the myeloid progenitors, not by the T and B lymphocytes, although it is expressed by circulating monocytes. 11 13 IL-1RAP, the accessory protein of the IL-1 receptor, plays a crucial role in immunity, inflammation, and cancer. It is involved in a tumor microenvironment that favors leukemia proliferation, 15 16 potentiates multiple oncogenic signaling pathways and oncogenic pathways, and contributes to AML oncogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…To identify regulators which are essential for metastasis, Zhang et al, utilized proteomic approaches and revealed a significant up-regulation of IL1RAP in cells resistant to anoikis (detachment-induced death) [ 116 ]. From this study, IL1RAP was identified as a direct target of EWSR1-FLI1 and a key driver of metastasis in EwS.…”
Section: The Transcriptional Regulation Mediated By Ewsr1-fli1mentioning
confidence: 99%